Using Character Maps to Learn English Literature - David T. Teh (The English Teacher, 2021)
Learning English literature has always been a challenge, as it demands advanced analytical skills, especially when learners are expected to critically analyse and discuss literary texts. Character mapping is proposed as a technique that develops analytical and critical thinking skills among learners. Drawing theoretical basis from cognitive science, constructivism, and cognitive stylistics, character mapping helps learners visualise connections between characters and events in a literary narrative, which then allows better comprehension of the literary text. 18 respondents from a Form 4 secondary school in Sabah, Malaysia, participated in a small-scale action research study. First, their previous experiences learning English literature was extrapolated via a need analysis, after which the respondents were then exposed to character mapping and its underlying principles. Then, they were asked to reflect and provide feedback on their experiences learning English literature using character maps. The feedback indicated positive support from the respondents, suggesting that character mapping can help learners learn English literature more effectively. Key observations include enhanced levels of comprehension, engagement, creativity, memory retention and organisation of thoughts. Two negative feedback were observed: (i) character mapping is time- consuming, and (ii) overusing character mapping might impede learning engagement. Future studies need to recruit larger sample population and potentially an experimental paradigm to investigate the impact of character mapping in greater detail.